Review of GaN HEMT High Power Amplifiers for Microwave Applications - Vivek V. Ratnaparkhi, Anil S. Hiwale (International Journal of Advanced Science and Technology, 2020)
Gallium Nitride (GaN) high power amplifiers become very popular in recent years for RF and microwave applications. There is huge interest in design and development of GaN high power amplifiers. In certain microwave applications GaN power amplifiers have already replaced conventional travelling wave tube amplifiers (TWTAs). This paper summarizes about different power devices and semiconductor technologies used for power amplification with emphasis on GaN technology. Various advantages of GaN power amplifiers with other power amplifier technologies are addressed. Often used performance improvement techniques in solid state power amplifiers (SSPAs) for microwave applications are discussed. This paper also describes some examples of GaN high electron mobility transistor (HEMT) power amplifier for microwave applications. Keywords: Gallium Nitride (GaN); Radar, Solid State Power Amplifier (SSPA), Travelling Wave Tube (TWT).